Critical Factors of Sustainable Procurement for Sustainable Project Development - Zailail, Natasya Arina (IRC, 2019)
Sustainability plays a huge role in light of Malaysia’s 2020 vision. In light of Malaysia concerns on environmental sustainability, construction industry is no doubt has become a major target for the global sustainability agenda. Previously, the implementation of sustainable procurement can be consider hard to be practice in Malaysia due to several reasons such as limited or lack of expose knowledge towards sustainable procurement.